(untitled) (The Pakistan Development Review, 1978)
Until recently it was conventional to treat the money stock as a policy variable exogenously determined by the central bank of a country. However, the notion that the money stock is jointly determined by the central bank, the commercial banks, and the nonbank public has gained general acceptance among economists. Thus regarded as an endogenous variable, the problem of choosing that model of money stock determination which provides the best predictions of its values in the immediate future assumes importance. It is the purpose of this paper, then, to formulate alternative models of the Pakistani money stock process and determine which of them yields the best short-run predictions. The existing models are of two basic types: money multiplier models of various degrees of sophistication, in which the money stock is obtained as the product of a stock of base money and an appropriate multiplier; and an empirical money supply equation used by Gibson [9]. These are discussed in first section of the paper.